Formy świadczeń oraz systemy finansowania polityki społecznej w krajach europejskich - Raczkowska, Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2009)
Wrocław Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 262-270 The paper analyzes the forms of benefits and systems for financing social protection in European Union countries. Research includes European Union countries and European Free Trade Association countries (EFTA) - Iceland, Norway, and Switzerland. In a social benefits structure the majority of the benefits are those paid in cash - more than 65% of the average amount. Different countries have markedly different systems for financing social protection, depending on whether they favour social security contributions (59.0% of total receipts at EU-27 level in 2005) or general government funding (37.6%)